Determination method of hydrogen embrittlement characteristic

The method addresses the inaccuracies and inefficiencies of conventional hydrogen embrittlement testing by using actual part shapes and neutral rust removal, allowing for quick, accurate, and cost-effective determination of hydrogen embrittlement characteristics.

JP2025047632APending Publication Date: 2025-04-03SUBARU CORP
View PDF 2 Cites 0 Cited by

Patent Information

Application Number
JP2023156232
Authority / Receiving Office
JP · JP
Patent Type
Applications
Current Assignee / Owner
Filing Date
2023-09-21
Publication Date
2025-04-03

AI Technical Summary

Technical Problem

Conventional methods for determining hydrogen embrittlement characteristics of high-strength steel parts are inaccurate, time-consuming, and costly, as they use test pieces with shapes different from actual parts, require dangerous reagents, and involve lengthy preparation and testing processes.

Method used

A method involving the production of test pieces with fractured cross-sections from actual vehicle parts, followed by rusting and hydrogen embrittlement induction using shock waves in a neutral rust removal liquid, allowing for the determination of hydrogen embrittlement characteristics based on crack formation.

Benefits of technology

This method enables rapid, accurate, and cost-effective evaluation of hydrogen embrittlement characteristics, considering both steel grade and part shape, without the need for dangerous reagents or extensive testing equipment.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure 2025047632000001_ABST
    Figure 2025047632000001_ABST
Patent Text Reader

Abstract

To solve the problems of a conventional determination method of a hydrogen embrittlement characteristic in which: preparing a test piece and performing a fatigue test requires a time; and it is difficult to reflect the test result to an actual component.SOLUTION: A determination method 10 of hydrogen embrittlement characteristic is given in which: a test piece 11 is prepared by using an actual component; ultrasonic excitation is applied to the test piece 11 with rust in neutral descaling liquid; and impact is applied to the test piece 11 while hydrogen is charged so that fatigue crack occurs due to hydrogen embrittlement. Through the determination method 10 of a hydrogen embrittlement characteristic, hydrogen embrittlement characteristic of high intensity steel used for a component repeatedly receiving load under a rust corrosive environment is determined in a short time with high accuracy and also safely determined without any dangerous reagent. Since a part of the actual component is used as the test piece 11, the determination result of the hydrogen embrittlement characteristic can be easily reflected to the actual component, and accuracy of the determination of the hydrogen embrittlement characteristic can be improved.SELECTED DRAWING: Figure 1
Need to check novelty before this filing date? Find Prior Art

Description

[Technical field]

[0001] The present invention relates to a method for determining hydrogen embrittlement characteristics. [Background technology]

[0002] In recent years, in order to reduce the weight of vehicles, the use of high-strength steel has been promoted for the actual parts mounted on the vehicles.

[0003] As a conventional method for determining the shear fatigue properties of a test piece of a metallic material under hydrogen penetration, for example, the method described in Patent Document 1 is known.

[0004] In the evaluation method of Patent Document 1, the shear fatigue properties are evaluated for metal materials used in machine elements that are subjected to torsional loads, etc. For this reason, a test specimen is prepared in advance with a shape suitable for the test specimen, with consideration given to the effect that as large a shear stress as possible will be applied to the surface of the smallest diameter part of the specimen.

[0005] Then, the test piece is charged with hydrogen in an aqueous solution of ammonium thiocyanate, and then fully reversed ultrasonic torsional vibration is applied to the test piece to determine the shear fatigue characteristics under hydrogen penetration.

[0006] Furthermore, as a conventional hydrogen embrittlement test solution and test method for steel materials, for example, the test method described in Patent Document 2 is known.

[0007] In the test method of Patent Document 2, the hydrogen embrittlement test solution contains an acetate buffer solution consisting of acetic acid and sodium acetate, and ammonium thiocyanate. The ammonium thiocyanate and acetic acid concentrations in the solution are within a predetermined concentration range, and the pH before the test is within a range of 4.0 to 5.0. After hydrogen charging is performed on a test material immersed in the hydrogen embrittlement test solution, the hydrogen embrittlement characteristics of the test material are judged based on the fracture time or the occurrence state of cracks. [Prior art documents] [Patent documents]

[0008] [Patent Document 1] JP 2011-191254 A [Patent Document 2] Patent No. 6575927 Summary of the Invention [Problem to be solved by the invention]

[0009] Conventional hydrogen embrittlement property evaluation methods have the problem that the difference in life span between steel types of high-strength steel parts is not accurately evaluated, and there are cases where high-strength steel parts are destroyed in an actual usage environment. This is thought to be because conventional hydrogen embrittlement property evaluation methods use test pieces with shapes different from those of actual high-strength steel parts, making it difficult to directly reflect the results of hydrogen embrittlement property evaluation on actual high-strength steel parts.

[0010] Therefore, a new method for assessing hydrogen embrittlement properties is needed that can assess hydrogen embrittlement properties by taking into account not only the hydrogen embrittlement properties of the steel type, but also the design stress and product hardness of the part shape.

[0011] Furthermore, in the conventional hydrogen embrittlement property evaluation method, it takes about 3 to 4 weeks to prepare a test piece with a shape suitable for a fatigue testing device. Furthermore, it takes about 2 to 4 weeks to perform fatigue tests such as rotating bending and tension / compression using the fatigue testing device. As a result, the conventional hydrogen embrittlement property evaluation method has a problem in that it is difficult to evaluate hydrogen embrittlement property easily and in a short time.

[0012] Furthermore, in order to carry out the above-mentioned fatigue test, the conventional hydrogen embrittlement property assessment method requires the preparation of a fatigue test device that performs rotary bending, tension and compression on the test piece, etc., which results in a problem of high test costs.

[0013] In addition, the conventional hydrogen embrittlement characteristic evaluation method has the problem that the acid solution used for hydrogen charging is somewhat dangerous to handle, and the conventional hydrogen embrittlement characteristic evaluation method has the problem that it takes time to determine the conditions for obtaining a predetermined hydrogen charge amount in the test piece.

[0014] In addition, the conventional hydrogen embrittlement property evaluation method has a problem that hydrogen charged in the test piece is released into the atmosphere as the test piece heats up and as time passes during fatigue testing, which may hinder brittle fracture. Therefore, in order to suppress the hydrogen release, measures such as air cooling or intermittent operation are required during fatigue testing.

[0015] The present invention has been made in consideration of the above circumstances, and has an object to determine, in a short time and with high accuracy, the hydrogen embrittlement properties when high-strength steel is used for parts that are repeatedly subjected to loads in a rust-corrosive environment. [Means for solving the problem]

[0016] A hydrogen embrittlement characteristic assessment method according to one embodiment of the present invention is characterized by comprising: a test specimen preparation step of fractured an actual part to be assembled to a vehicle to prepare a test specimen having a fracture surface; a rust imparting step of imparting rust to the fracture surface of the test specimen; a hydrogen embrittlement step of immersing the test specimen in a neutral rust remover and applying shock waves to the test specimen to hydrogen embrittle the fracture surface of the test specimen; and a hydrogen embrittlement characteristic assessment step of assessing the hydrogen embrittlement characteristic of the test specimen using the amount of cracks generated on the fracture surface of the test specimen. Effect of the Invention

[0017] In one embodiment of the present invention, a hydrogen embrittlement property evaluation method uses an actual part to prepare a test piece, which is then subjected to ultrasonic vibration in a neutral rust remover. An impact is then applied to the test piece while charging it with hydrogen, causing fatigue cracks due to hydrogen embrittlement, and the hydrogen embrittlement property of the test piece is evaluated using the amount of cracks. This hydrogen embrittlement property evaluation method allows the hydrogen embrittlement property of high-strength steel used in a part that is repeatedly subjected to load in a rust-corrosive environment to be evaluated safely in a short time with high accuracy and without the use of dangerous reagents. [Brief description of the drawings]

[0018] [Figure 1]1 is a flowchart illustrating a hydrogen embrittlement characteristic assessment method according to an embodiment of the present invention. [Figure 2A] FIG. 2 is a diagram illustrating a fracture surface of a test piece of steel type A after 72 hours of ultrasonic vibration in a hydrogen embrittlement property evaluation method according to one embodiment of the present invention. [Figure 2B] FIG. 2 is a diagram illustrating a fracture surface of a test piece of steel type B after 72 hours of ultrasonic vibration in a hydrogen embrittlement property evaluation method according to one embodiment of the present invention. [Figure 3A] FIG. 2 is a diagram illustrating a fracture surface of a test piece of steel type A after 10 hours of ultrasonic vibration in a hydrogen embrittlement property evaluation method according to one embodiment of the present invention. [Figure 3B] FIG. 2 is a diagram illustrating a fracture surface of a test piece of steel type B after 10 hours of ultrasonic vibration in a hydrogen embrittlement property evaluation method according to one embodiment of the present invention. [Figure 4] FIG. 1 is a diagram for explaining a hydrogen embrittlement property evaluation method according to one embodiment of the present invention, and is a graph showing the amount of cracks generated on the fracture surface of each steel type after 72 hours of ultrasonic vibration. [Diagram 5] FIG. 2 is a diagram for explaining a hydrogen embrittlement property evaluation method according to one embodiment of the present invention, and is a graph showing the amount of cracks generated on the fracture surface of each steel type after 10 hours of ultrasonic vibration. [Figure 6] 1 is a flowchart illustrating a conventional method for determining hydrogen embrittlement characteristics. DETAILED DESCRIPTION OF THE PREFERRED EMBODIMENTS

[0019] Hereinafter, a hydrogen embrittlement characteristic assessment method 10 according to one embodiment of the present invention will be described in detail with reference to the drawings. In the description of this embodiment, the same reference numbers are used for the same members in principle, and repeated description will be omitted.

[0020] FIG. 1 is a flow chart for explaining each step of the hydrogen embrittlement property evaluation method 10 of the present embodiment. FIG. 2A is a diagram for explaining a fracture surface 12 after 72 hours of ultrasonic vibration is applied to a test piece 11 of steel type A by the hydrogen embrittlement property evaluation method 10 of the present embodiment. FIG. 2B is a diagram for explaining a fracture surface 12 after 72 hours of ultrasonic vibration is applied to a test piece 11 of steel type B by the hydrogen embrittlement property evaluation method 10 of the present embodiment. FIG. 3A is a diagram for explaining a fracture surface 12 after 10 hours of ultrasonic vibration is applied to a test piece 11 of steel type A by the hydrogen embrittlement property evaluation method 10 of the present embodiment. FIG. 3B is a diagram for explaining a fracture surface 12 after 10 hours of ultrasonic vibration is applied to a test piece 11 of steel type B by the hydrogen embrittlement property evaluation method 10 of the present embodiment. FIG. 4 is a graph for explaining the amount of cracks after 72 hours of ultrasonic vibration is applied to a test piece 11 by the hydrogen embrittlement property evaluation method 10 of the present embodiment. Fig. 5 is a graph illustrating the amount of cracks after ultrasonic vibration was applied to a test piece 11 for 10 hours by the hydrogen embrittlement property evaluation method 10 of this embodiment. Note that, although Fig. 2A to Fig. 3B show the test pieces 11 of steel type A and steel type B for explanation, the test piece 11 of steel type C was also subjected to a test by the same process, and the fracture surface 12 was observed.

[0021] As shown in FIG. 1 , the hydrogen embrittlement assessment method 10 of this embodiment includes a test piece preparation process of preparing a test piece 11 by fracture of a member made of high-strength steel, a rust imparting process of imparting rust to the test piece 11, a hydrogen embrittlement process of applying shock waves to the test piece 11 in a neutral rust remover, and a hydrogen embrittlement characteristic assessment process of assessing the hydrogen embrittlement characteristics from the amount of cracks on the fracture surface 12 of the test piece 11.

[0022] First, the test piece preparation process will be described. In the test piece preparation process, a mechanical stress is applied to a member made of high strength steel to break the member, thereby preparing a test piece 11.

[0023] Here, an example of a member made of high-strength steel is an actual part to be installed in a vehicle, and the actual part itself may be used or a part of the actual part may be cut and used. By using a high-strength steel part having the same shape as the actual part and breaking it, as the test piece 11, it becomes possible to determine the hydrogen embrittlement property taking into account not only the hydrogen embrittlement property due to the steel type, but also the design stress and product hardness due to the part shape.

[0024] In this embodiment, the actual part used as the test piece 11 is a part that is repeatedly subjected to a load in a rust-corrosive environment, such as while a vehicle is running. Examples of the actual part include a coil spring and a leaf spring of a vehicle.

[0025] The high-strength steel of the present embodiment is defined by the Japan Society of Mechanical Engineers as high-strength steel such as high-tensile steel, tough steel, and ultra-high-strength steel. Tough steel is used for machine structural parts that require strength and toughness, and is strengthened by quenching and toughened by tempering. High-strength steel is generally defined as steel with a tensile strength of 1300 MPa or more.

[0026] In the hydrogen embrittlement property evaluation method 10 of this embodiment, the following three types of steel type A, steel type B, and steel type C are prepared as high strength steels. Steel type A is a steel containing iron, carbon, silicon, manganese, copper, nickel, and chromium. Steel type B is a steel containing iron, carbon, silicon, manganese, copper, nickel, chromium, titanium, and vanadium. Steel type C is a steel containing iron, carbon, silicon, manganese, copper, nickel, chromium, and titanium.

[0027] In the test piece preparation step, an impact tester or a universal testing machine is used to break the actual part made of high strength steel to prepare the test piece 11. Alternatively, the actual part made of high strength steel is simply broken by clamping it with a vice to prepare the test piece 11. In the test piece preparation step, a notch may be made in the actual part made of high strength steel before breaking in order to shorten the breaking time.

[0028] The shape of the test piece 11 is not particularly limited as long as it can be immersed in the water tank of the ultrasonic vibrator in the hydrogen embrittlement process. When comparing the life differences between multiple steel types A to C, it is desirable to standardize the weight and shape of each test piece 11.

[0029] Next, the rust imparting step will be described. In the rust imparting step, rust is imparted to the fracture surface 12 of the test piece 11 prepared in the previous step by a corrosion test.

[0030] As the corrosion test, a known test such as a salt water combined cycle test or a salt spray test is used. The test time is the time required for rust to develop on the entire fracture surface 12, and may usually be about 24 hours. In this embodiment, the test pieces 11 made from the above steel types A, B, and C are each corroded for 24 hours to develop rust on the fracture surface 12 of each test piece 11.

[0031] Next, the hydrogen embrittlement process will be described. In the hydrogen embrittlement process, the test piece 11 to which rust has been applied in the previous process is placed in a water tank filled with a neutral rust remover, and shock wave vibration is applied to the test piece 11 in the neutral rust remover.

[0032] The neutral rust remover may be a commercially available neutral rust remover. The neutral rust remover contains thioglycolic acid and thioglycolic acid salts (ammonium thioglycolic acid salt, diammonium thioglycolic acid salt, etc.) as active rust remover ingredients. The active rust remover ingredients may be used alone or in combination of two or more. It is particularly preferable to use a neutral rust remover containing ammonium thioglycolic acid salt. The neutral rust remover may contain other ingredients such as a surfactant and a chelating agent.

[0033] The shock wave excitation is performed using an ultrasonic vibrator such as a commercially available eyeglass cleaning machine. Although it depends on the performance of the ultrasonic vibrator used, an excitation frequency of 10 kHz to 80 kHz can be used without any problems. In order to stably generate cracks in the test piece 11, the excitation time is 10 hours to 72 hours. Note that the time required for hydrogen embrittlement can be shortened by increasing the excitation frequency of the ultrasonic vibrator.

[0034] In this embodiment, by immersing test pieces 11 made from a plurality of steel types A to C in the neutral rust remover, the previously applied rust Fe2O3 is removed as shown in the following reaction formula (1), and hydrogen is generated on the surface of the fracture surface 12 during the reaction as shown in the following reaction formula (2).

[0035] [ka]

[0036] In the hydrogen embrittlement process, as shown in the above reaction formulas (1) and (2), shock wave vibration is performed while continuing to charge hydrogen onto the surface of the fracture surface 12 of the test piece 11. Then, shock waves of liquid bubbles caused by ultrasonic vibration are repeatedly applied to the fracture surface 12 of the test piece 11, so that hydrogen embrittlement can progress in a short period of time.

[0037] In the conventional method, fatigue testing required about two to four weeks, but in this embodiment, cracks due to hydrogen embrittlement can be stably generated on the fracture surface 12 of the test piece 11 within three days.

[0038] As described above, in the hydrogen embrittlement process of this embodiment, the method of ultrasonically vibrating the test piece 11 in a neutral rust remover eliminates the need for an acid immersion process of the test piece 11 for hydrogen charging. This eliminates the need to use ammonium thiocyanate or the like, which is dangerous to handle, and allows the test piece 11 to be safely charged with hydrogen.

[0039] In addition, since hydrogen continues to be charged in the test piece 11 during shock wave excitation, there is no need for measures to suppress hydrogen release such as air cooling or intermittent operation. Furthermore, since the test piece 11 is constantly cooled in liquid during the hydrogen embrittlement process, there is no need for measures to prevent the hydrogen charged in the test piece 11 from being released into the atmosphere.

[0040] Furthermore, by using a neutral rust remover, hydrogen embrittlement of the test piece 11 progresses relatively slowly, so the difference in the amount of cracks between steel types A to C becomes more clearly apparent.

[0041] Next, the hydrogen embrittlement property evaluation step will be described. In the hydrogen embrittlement property evaluation step, the hydrogen embrittlement property is evaluated from the amount of cracks generated on the fracture surface 12 of the test piece 11. The amount of cracks is measured by observing the fracture surface of the test piece 11.

[0042] 2A to 3B, for example, the entire fracture surface 12 of the test piece 11 is observed, and the location with the most cracks is selected as the evaluation location by an operator's visual inspection. Then, for example, scale marks are drawn vertically and horizontally at equal intervals of 0.1 mm per square at the selected evaluation location to create a grid. Thereafter, the number of intersections where the cracks at the evaluation location intersect with the scale marks is counted, and this number of cracks is used as the crack amount to evaluate the hydrogen embrittlement characteristics.

[0043] In this embodiment, the squares are quantified measurement areas of 4 mm squares with a length and width of 2.0 mm. The size of each square and the measurement area can be arbitrarily changed in design depending on the area of ​​the fracture surface 12 of the test piece 11, the state of the cracks, and the like. The selection of the judgment point is not limited to a selection method based on visual inspection by an operator. For example, an image analyzer may be used to observe the entire fracture surface 12 of the test piece 11, and an area with a high density of cracks may be image-analyzed and selected as the judgment point. The length of the cracks in the judgment point may be measured by image analysis of the fracture surface 12.

[0044] As shown in the figure, it was confirmed that the test piece 11 made of steel type A had a larger amount of cracks than the test piece 11 made of steel type B and the test piece 11 made of steel type C, both when the vibration time of the test piece 11 was 72 hours and when it was 10 hours.

[0045] Next, a threshold value k for satisfying the criteria for pass / fail judgment of hydrogen embrittlement properties is set as shown in Figures 4 and 5. Then, the hydrogen embrittlement properties of the test specimens 11 made from each of steel types A to C are judged based on whether the amount of cracks in the test specimens 11 measured in Figures 2A to 3B exceeds the threshold value k.

[0046] Here, an example of the procedure for setting the threshold value k will be described. Based on past breakage occurrence data, at least one steel type is selected from steel types with a high breakage occurrence rate, and at least one steel type is selected from steel types with a low breakage occurrence rate. Next, the hydrogen embrittlement property evaluation method 10 of the present embodiment described above is performed on the selected steel types to measure the crack amount of each steel type. Then, a crack amount threshold value k that satisfies the evaluation criteria is set between the minimum crack amount of the steel type with a high breakage occurrence rate and the maximum crack amount of the steel type with a low breakage occurrence rate.

[0047] As shown in the figure, the amount of cracks in steel type A exceeds the threshold k, so steel type A is judged to be a failed steel type. On the other hand, the amount of cracks in steel types B and C are less than the threshold k, so steel types B and C are judged to be passed steel types. In addition, even if a steel type satisfies the pass criteria, as shown in FIG. 5, steel type C has a crack amount after 10 hours of vibration that is closer to the threshold k, so it can be judged that steel type B has better hydrogen embrittlement properties than steel type C. Note that there is a correlation between the amount of cracks generated in test piece 11 by hydrogen embrittlement property judgment method 10 of this embodiment and the breakage occurrence rate of actual parts when subjected to repeated loads in the market.

[0048] As described above, the hydrogen embrittlement property assessment method 10 of the present embodiment makes it possible to safely evaluate the hydrogen embrittlement property of an actual high-strength steel component in a short time, with high accuracy, and without using dangerous reagents.

[0049] 6 is a flow chart for explaining a conventional hydrogen embrittlement property assessment method 20. As shown in the figure, the conventional hydrogen embrittlement property assessment method 20 includes a test piece preparation step of preparing a test piece 11 having a shape suitable for fatigue testing, a step of hydrogen charging the test piece by acid immersion, salt water corrosion testing or the like, and a step of performing fatigue tests such as rotary bending and tension / compression on the hydrogen-charged test piece to evaluate the life until the test piece breaks.

[0050] In the conventional evaluation method, the preparation of test pieces and the fatigue test required a total of about 5 to 8 weeks, but in the hydrogen embrittlement property evaluation method 10 of the present embodiment, the entire process can be performed in about 2 to 5 days, and the time required for hydrogen embrittlement property evaluation can be significantly shortened. For example, the preparation of test pieces in the conventional method takes about 3 to 4 weeks, but the test piece preparation process of the hydrogen embrittlement property evaluation method 10 can be completed in about 1 day by using actual parts. Furthermore, the conventional fatigue test takes about 2 to 4 weeks per steel type, but the hydrogen embrittlement process of the hydrogen embrittlement property evaluation method 10 can be completed in about 3 days.

[0051] Moreover, the hydrogen embrittlement property assessment method 10 of the present embodiment does not require mechanical fatigue testing such as rotary bending or tension / compression, as in the conventional assessment methods described above. As a result, a fatigue testing device is not required, and the assessment cost of the hydrogen embrittlement property assessment method 10 is significantly reduced.

[0052] Furthermore, in the hydrogen embrittlement property assessment method 10 of this embodiment, since a fatigue testing device is not required, there are no restrictions on the shape of the test piece 11, and it becomes possible to use an actual component or a part of an actual component as the test piece 11. As a result, it becomes possible to assess hydrogen embrittlement property taking into account not only the hydrogen embrittlement property according to the steel type, but also the design stress and product hardness according to the component shape.

[0053] The present invention is not limited to the above-mentioned embodiment, and the same effect as the above can be obtained by appropriately setting the composition of the neutral rust remover, the vibration frequency, and other conditions so that the difference in the amount of cracks between the steel types becomes clear. In addition, various modifications are possible within the scope of the present invention. [Explanation of symbols]

[0054] 10. Hydrogen embrittlement characteristic evaluation method 11 Test specimen 12 Fracture surface 20 Hydrogen embrittlement characteristic evaluation method

Claims

1. a test piece preparation step of fracture-cutting an actual part to be assembled to a vehicle and preparing a test piece having a fractured surface; a rust imparting step of imparting rust to the fracture surface of the test piece; a hydrogen embrittlement process in which the test piece is immersed in a neutral rust remover and shock waves are applied to the test piece to hydrogen embrittle the fracture surface of the test piece; and a hydrogen embrittlement characteristic assessment step of assessing the hydrogen embrittlement characteristic of the test piece using the amount of cracks generated on the fracture surface of the test piece.

2. 2. The method for evaluating hydrogen embrittlement characteristics according to claim 1, wherein the actual part is a member made of high strength steel and is subjected to repeated loads from the vehicle.

3. 2. The method for evaluating hydrogen embrittlement characteristics according to claim 1, wherein in the hydrogen embrittlement step, the shock waves are applied to the test piece using an ultrasonic vibration device.

4. 4. The hydrogen embrittlement characteristic assessment method according to claim 1, wherein in the hydrogen embrittlement characteristic assessment step, the amount of cracks generated on the fracture surface of the test piece is measured, the amount of cracks is compared with a predetermined threshold value, and if the amount of cracks is less than the threshold value, it is determined that the test piece satisfies the pass criterion for the hydrogen embrittlement characteristics.

Citation Information

Patent Citations

  • Method for evaluating shear fatigue characteristic of metal material applied with rolling contact and torsional load and having penetrated hydrogen

    JP2011191254A

  • Hydrogen embrittlement test solution for steel using ammonium thiocyanate and test method

    JP6575927B2